Characteristics of Planococcus antioxidans sp. nov., an antioxidant‐producing strain isolated from the desert soil in the Qinghai–Tibetan Plateau. Issue 6 (11th March 2020) - Zhang, Binglin; Yang, Ruiqi; Zhang, Gaosen; Liu, Yang; Zhang, Dongming; Zhang, Wei; Chen, Tuo; Liu, Guangxiu
Abstract: Strain Y74 T was an isolate from the sandy soil in the town of Huatugou, Qinghai–Tibet Plateau, China. An analysis of this strain's phenotypic, chemotaxonomic, and genomic characteristics established the relationship of the isolate with the genus Planococcus . Strain Y74 T was able to grow between 4 and 42°C (with an optimum temperature of 28°C) at pH values of 6–8.5 and in 0%–7% (w/v) NaCl. The dominant quinones were MK‐8 and MK‐7. The polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, and an unknown phospholipid. The majority of the fatty acid content was anteiso‐C15:0 (28.8%) followed by C16:1 ω7c alcohol (20.9%) and iso‐C14:0 (13.4%). The 16S rRNA gene sequence similarity analysis demonstrated a stable branch formed by strain Y74 T and Planococcus halotolerans SCU63 T (99.66%). The digital DNA–DNA hybridization between these two strains was 57.2%. The G + C content in the DNA of Y74 T was 44.5 mol%. In addition, the morphological, physiological, and chemotaxonomic pattern clearly differentiated the isolates from their known relatives. In conclusion, the strain Y74 T (=JCM 32826 T  = CICC24461 T ) represents a novel member of the genus Planococcus, for which the name Planococcus antioxidans sp. nov. is proposed. Strain Y74 T was found to have potent antioxidant activity via its hydrogen peroxide tolerance and its 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical‐scavenging activity. The DPPH radical‐scavenging activity was determined to be 40.2 ± 0.7%. The genomic analysis indicated that six peroxidases genes, one superoxide dismutase gene, and one dprA (DNA‐protecting protein) are present in the genome of Y74 T . Abstract : In this study, we reported a novel strain isolated from the desert soil in the Qinghai–Tibetan Plateau. According to an analysis of phenotypic, phylogenetic, and chemotaxonomic characteristics, strain Y74T was determined to be a new member within the genus Planococcus. Therefore, it was named as Planococcus antioxidans sp. nov. Y74T. Strain Y74T was found to have potent antioxidant activity via its hydrogen peroxide tolerance and its 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical‐scavenging activity.